Tegument Protein pUL47 Is Important but Not Essential for Horizontal Transmission of Vaccinal Strain SB-1 of Gallid Alphaherpesvirus 3 - Motoyuki Esaki; Mélanie Chollot; Sylvie Rémy; Katia Courvoisier-Guyader; Zoltan Penzes; David Pasdeloup; Caroline Denesvre (Viruses)
The gallid alphaherpesvirus 3 (GaAHV3) SB-1, a Mardivirus used as a vaccine against Marek’s disease, has been proposed as an interesting viral vector for poultry vaccination. However, SB-1 is highly transmissible between chickens, a feature that may be a limitation for the use of live recombinant vaccines. We have previously shown that UL47 is essential for horizontal transmission of the pathogenic Marek’s disease virus between chickens, but it is completely dispensable for replication and pathogenesis. In contrast, the role of UL47 in the biology of SB-1 remains unknown. To study that, we generated an SB-1 mutant lacking UL47 (∆47) from a commercial SB-1 isolate. This mutant replicated and spread like the WT in primary fibroblasts, indicating no growth defects in cell culture. In vivo, chickens inoculated with ∆47 had significantly reduced viral loads in the blood and the spleen, and transport to the skin was delayed compared to WT inoculated chickens. Strikingly, the ∆47 mutant was present in 66% of contact birds. As expected, 100% of contact birds were positive for the WT. In conclusion, our findings reveal that UL47 facilitates GaAHV3 SB-1 replication in vivo, which is important for latency establishment but is not essential for horizontal transmission, unlike for MDV.